Unraveling the role of cancer-associated fibroblasts in B cell lymphoma - Mukherjee, Prithviraj; Ansell, Stephen M.; Mondello, Patrizia (Frontiers in Immunology, 2024)
Recent breakthroughs in research have sparked a paradigm shift in our understanding of cancer biology, uncovering the critical role of the crosstalk between tumor cells and the immune cells of the tumor microenvironment (TME) in malignant transformation. Fibroblasts have long been viewed as ancillary participants in cancer progression, often eclipsed by the prominence given to malignant cells. Novel investigations, however, have increasingly acknowledged the essential part played by the fibroblasts and their phenotypic doppelganger cancer-associated fibroblasts (CAFs) in fostering immunosuppression and promoting tumor progression. Here we review the cell-of-origin from which CAFs derive and their altered programs compared to their normal counterpart. We will also discuss the complex interplay between CAFs and the surrounding immune cells of the TME in the context of solid tumors and B cell lymphomas, with a focus on the "reprogrammable" role of CAFs in immunosuppression, immuno-activation and immuno-avoidance, and their implications on drug resistance. Finally, we will examine the existing and plausible therapeutic approaches targeting CAFs as a strategy to enhance treatment response.